The organizational climates of five selected schools of nursing in one of the cities in the Central Visayas Region - Lomantas, Priscilla Andoy 1938-
This study utilized the perceptions of all the 65 nurse instructors in five schools as expressed through Halpin's (1966) Organizational Climate Description Questionnaire and an interview schedule. School climates are more inclined to be controlled, closed and paternalistic. Disengagement is high where there is a rapid turnover among nurse-instructors due to dissatisfaction caused by low salaries or salaries not commensurate to qualification and experience, absence or lack of clear-cut job descriptions and the school system is too centralized with few delegated responsibilities. The school principals are viewed as aloof, with low consideration towards their instructors and whose way of trying to move the organization is through frequent reminders to work harder. The prevailing high faculty morale is attributed to task-accomplishment rather than to social need satisfaction.